PENGARUH POLA MENONTON CERAMAH USTAD FELIX SIAUW MELALUI INSTAGRAM TERHADAP TOLERANSI PERBEDAAN PENDAPAT UMAT ISLAM (STUDI PADA FOLLOWERS AKUN @FELIXSIAUW) - Nadzim, Muhammad; Walisyah, Tengku (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
There are many people, especially Muslim people who carry out da'wah activities using the Instagram application. This is evidenced by the emergence of many da'wah accounts in the Instagram application that contain video content and writings for preaching. These contents contain discussion of monotheism, fiqh, Islamic politics, and others. Researchers used quantitative research techniques pre experimental design (Non Design). The population in this study are all @Felixsiauw Account Followers. research sample of 100 respondents. The method used to collect information in this research is using a questionnaire or questionnaire and documentation. In accordance with the results of this study, it can be concluded that there is an impact from the pattern of watching Ustad Felix Siauw's lectures through Instagram on tolerance for differences in Muslim opinion (Stussi on Account Followers @Felixsiauw. This can be seen in the hypothesis test with the t-test, this finding is proven through the magnitude of the beta coefficient is 0.729 and the significant coefficient is 0.000 which is smaller than 0.05.